Recombinant Human Follicle-Stimulating Hormone in Controlled Ovarian Hyperstimulation with Assisted Reproductive Technology in China: A Cost-Effectiveness Analysis - Li H; He W; Lin H; Du A; Zhang X; Yang H; Qu S (Dove Medical Press, 2024)
Hongchao Li,1 Wei He,2 Hongbo Lin,3 Angying Du,4 Xue Zhang,5 Han Yang,5 Shuli Qu5 1School of International Pharmaceutical Business, China Pharmaceutical University, Nanjing, 211198, People's Republic of China; 2Fertility and Reproductive Medicine Centre, The Southwest Hospital of AMU, Chongqing, 400038, People's Republic of China; 3Department of Reproductive Medicine, Peking University Shenzhen Hospital, Shenzhen, 518036, People's Republic of China; 4Merck Serono, an Affiliate of Merck KGaA Darmstadt Germany, Beijing, 100016, People's Republic of China; 5Real-World Solutions, IQVIA, Shanghai, 200041, People's Republic of ChinaCorrespondence: Shuli Qu, Real-World Solutions, IQVIA, 1359 Yaolong Road, Shanghai, People's Republic of China, Email shuli.qu1@iqvia.comBackground: To compare the cost-effectiveness of originator (reference) recombinant human follicle stimulating hormone alfa (rhFSH-α) (follitropin alfa, GONAL-f) and its biosimilar (rhFSH, JinSaiHeng) in assisted reproductive technology (ART) from a Chinese patient perspective.Methods: A decision tree model was developed to simulate the treatment pathway of infertile women undergoing ART using GONAL-f or JinSaiHeng. Published clinical and cost data were used to evaluate the cost-effectiveness of the rhFSH-α. The cumulative live birth rate (CLBR), direct medical costs and costs per cumulative live birth were estimated via an analytic decision-tree model.Results: CLBR of GONAL-f was higher than JinSaiHeng preparation (88.3% vs 84.4%), while the cost per cumulative live birth was lower (51,475 vs 52,095 CNY).Conclusion: The originator rhFSH-α was associated with higher CLBR and lower cost per cumulative live birth, with incremental cost per additional live birth of 38,096 CNY (Chinese Yuan).Keywords: recombinant human follicle stimulating hormone, controlled ovarian stimulation, assisted reproductive technology, cost-effectiveness analysis